Analisis Koordinasi Tim Unit Apron Movement Control (AMC) Dalam Penanganan Parkir Pesawat di Bandar Udara Sultan Hasanuddin Makassar - Hety Nia Marwati (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study aims to determine how to determine aircraft parking stands at Sultan Hasanuddin Airport Makassar, how to coordinate the AMC unit team in handling aircraft parking, to find out the obstacles faced, to find out the efforts made by AMC officers to overcome problems when handling aircraft parking stands. This research uses a qualitative research type. The data used in the form of primary data and secondary data. Data analysis used a qualitative descriptive method with the Miles and Huberman model, namely reducing data, presenting data, and drawing conclusions/verification. Test the validity of the data using the triangulation method. The results showed that AMC officers had fully coordinated with related units in handling aircraft parking, but there were several obstacles such as oil/fuel spills on the apron and lack of coordination between airlines and AMC units, as well as departure and arrival schedules that were not in accordance with the schedule. Efforts made by AMC officers are optimizing the use of aircraft parking stands, communicating and coordinating well with related parties, and always conducting routine inspections in the apron area.